2019
DOI: 10.3390/ani9040143
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Insect Meal from Hermetia illucens Prepupae on Autochthonous Gut Microbiota of Rainbow Trout (Oncorhynchus mykiss)

Abstract: This study evaluated the effects of dietary insect meal from Hermetia illucens larvae on autochthonous gut microbiota of rainbow trout (Oncorhynchus mykiss). Three diets, with increasing levels of insect meal inclusion (10%, 20%, and 30%) and a control diet without insect meal were tested in a 12-week feeding trial. To analyze the resident intestinal microbial communities, the Illumina MiSeq platform for sequencing of 16S rRNA gene and QIIME pipeline were used. The number of reads taxonomically classified acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
156
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(188 citation statements)
references
References 58 publications
29
156
3
Order By: Relevance
“…Our results corroborate previous findings in rainbow trout revealing that mucosa-associated intestinal microbiota was less influenced by dietary inclusion of 30% black soldier fly larvae meal compared to digesta-associated intestinal microbiota (28,29). Results from molecular-based studies on salmonid intestinal microbiota hitherto suggest that diet modulates digesta-and mucosa-associated intestinal microbiota to varying degrees with the latter generally being more resilient to dietary interventions (19,(26)(27)(28)(29)35). As such, current practices of profiling only one of or a mixture of digesta-and mucosa-associated microbiota may obscure the response of intestinal microbiota to dietary changes.…”
Section: Significant Interactions Between Diet and Sample Origin Effectsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results corroborate previous findings in rainbow trout revealing that mucosa-associated intestinal microbiota was less influenced by dietary inclusion of 30% black soldier fly larvae meal compared to digesta-associated intestinal microbiota (28,29). Results from molecular-based studies on salmonid intestinal microbiota hitherto suggest that diet modulates digesta-and mucosa-associated intestinal microbiota to varying degrees with the latter generally being more resilient to dietary interventions (19,(26)(27)(28)(29)35). As such, current practices of profiling only one of or a mixture of digesta-and mucosa-associated microbiota may obscure the response of intestinal microbiota to dietary changes.…”
Section: Significant Interactions Between Diet and Sample Origin Effectsupporting
confidence: 92%
“…While studies in mammals and fish have revealed substantial differences between the digesta-and mucosa-associated intestinal microbiota (19,(22)(23)(24)(25), most studies investigating diet effects on the intestinal microbiota of fish have sampled the digesta only or a mixture of digesta and mucosa. Evidence is accumulating that digesta-and mucosa-associated intestinal microbiota in fish respond differently to dietary changes (19,(26)(27)(28)(29). Profiling only one of or a mixture of digestaand mucosa-associated microbiota may obscure the response of intestinal microbiota to dietary changes.…”
Section: Introductionmentioning
confidence: 99%
“…From a nutritional point of view, IM are rich in proteins, with a good essential amino acid (EAA) profile, and they have a good content of fat, vitamins, and minerals [15]. In the last few years, the potential of IM as partial or complete replacer of FM has been investigated [15] with interesting results both in freshwater fish such as rainbow trout (Oncorhynchus mykiss) [16,17], Siberian sturgeon (Acipenser baerii) [18,19], Jian carp (Cyprinus carpio var. Jian) [20], Yellow catfish (Pelteobagrus fulvidraco) [21], Nile tilapia (Oreochromis niloticus) [22,23] North African catfish (Clarias gariepinus) [24] and mandarine fish (Siniperca scherzeri) [25], and marine fish, as in European seabass (Dicentrarchus labrax) [26,27], gilthead sea bream (Sparus aurata) [28], Japanese seabass (Lateolabrax japonicus) [29], Atlantic salmon (Salmo salar) [30][31][32], and meagre (Argyrosomus regius) [33].…”
Section: Introductionmentioning
confidence: 99%
“…Also Mota de Carvalho et al 2019showed that powder of the yellow mealworm has a potential prebiotic effect. This prebiotic effect may be caused by the exoskeleton of insects, chitin (Komi et al 2018), not only in humans (Stull et al 2018) but also in fish (Rimoldi et al 2019;Terova et al 2019). Also insects have the largest repertoire of antimicrobial peptides, which has promoted their development as alternatives to conventional antibiotics, in an attempt to address…”
Section: Nutrition and Healthmentioning
confidence: 99%